Relationship between Psychological Empowerment with Affective Commitment among Nurses in Zanjan, 2010 - Fereidoun Eskandari; Mehrnoosh Pazargadi; Mansoureh Zagheri Tafreshi; Soheila Rabie Siahkali; Ali Reza Shoghli (Zanjan University of Medical Sciences and Health Services, 2014)
Background and Objectives: Nurses are the largest group of health workers whose professional abilities play important role in realization of health sector mission. Nurseschr('39') perceptions of their work environment forms their sense of empowerment and commitment to the organization. This study aimed to determine the relationship between psychological empowerment and affective commitment among nurses. Materials and Methods: In this descriptive-correlative study, 491 nurses working in Zanjan province hospitals were selected to the study in winter 2010. The data collection tool included the "Sprietzer psychological empowerment questionnaire" and the "organizational commitment questionnaire of Allen and Meyer". The validity and reliability of the questionnaire were assessed through appropriate methods. Data were analyzed using the ANOVA, t-test, Pearson correlation, and linear regression method in the SPSS-16. Results: Most of the participants (%90.6) were female. The mean age of the participants was 30.7 years. The mean score of the empowerment perception among %85.7 of nurses was high. The mean score of the affective commitment was moderate (3.17±0.88). The correlation and linear regression tests indicated that psychological empowerment was statistically correlate with the affective commitment of nurses and could predicted it. Conclusion: Based on the findings of this study, psychological empowerment was a predictive factor for affective commitment. In order to improve affective commitment of nurses, hospital managers should try to increase independency and participation of nurses in organizational decision-makings.